Credit counselling and debt management services in the United States - Gyeongmin Park (United Nations Research Institute for Social Development (UNRISD), 2023)
This scoping paper outlines credit counselling and debt management structures in the United States and their effectiveness in improving consumers' financial management status. First, various public and private credit counselling systems are explained with a focus on each institution's roles and functioning areas. Second, the overall results of credit counselling are assessed using reports from the National Foundation of Credit Counseling's Sharpen Your Financial Focus Initiative and non-profit credit counselling agencies located in multiple states. Due to the diversity of economic statuses in various states, state-level financial management structures are also incorporated. Additionally, several non-profit credit counselling agencies are assessed to identify the commonalities of good practices among money advice services. This scoping paper finds that while the United States' credit counselling service evaluation outcomes do help consumers resolve debt problems overall, a stricter evaluation and feedback process is required and measures to prevent deceptive actions by for-profit credit counselling agencies is critical. The lack of existing information concerning the effectiveness of credit counselling and consumer feedback after going through such services raises difficulties when defining the qualitative data and suggesting credit counselling and debt management system application methods. For a more valid analysis and strategy suggestion, a transparent information system and legislatures are needed.
Keywords: 330; Schuldenmanagement; Verbraucherberatung; Private Verschuldung; Öffentliche Schulden; Insolvenz; USA